Impact of elimination of dividend distribution tax on Indian corporate firms amid COVID disruptions - Anshu Agrawal (Journal of Risk and Financial Management, 2021)
Economic fallouts from COVID-19 have been unprecedented across all industries, with a handful of exceptions. The present study attempts to capture the impact of dividend distribution tax elimination, introduced through the Indian Finance Act 2020, on corporate dividend behavior in India. It explores the determinants of dividend payouts, changing payout decisions, dividend behavior of regular payers, and the prevalence of factors associated with changing payouts. Out of the top 1000 firms, based on their market capitalization at the Bombay Stock Exchange, 509 non-financial firms pursuing consistent dividend payments from 2015 to 2019 are analyzed. The study also examines the dividend behavior of regular payers exhibiting a stable or step-up payout from 2015 to 2019. COVID's impact on the firm's financial performance and sentiments seems to dominate, suppressing investors' expectations of enhanced payouts associated with dividend distribution tax advantages, with considerable reductions in payouts and omissions shown by regular and irregular payers in 2020 and 2021 vis-à-vis the preceding years. The findings signify that the dividend payouts of sample firms are positively associated with the firms' size, MBV ratio, and past dividends, and negatively allied with free cash flows and the EBITDA margin. Regular payers are observed to be more sensitive to past dividends. The study lends credence to the conservatism and prevalence of signaling and catering theories in the dividend behavior of Indian corporate firms.
Keywords: 330; COVID-19 economic disruptions; DDT amendment; dividend cuts; dividend payout; Indian Finance Act 2020; omission; regular payers